Space, time and number in the brain : searching for the foundations of mathematical thought : an attention and performance series volume - Attention and Performance (Symposium) 2010 : Cernay-la-Ville, France); Dehaene, Stanislas; Brannon, Elizabeth; ScienceDirect eBooks (San Diego : Elsevier Academic Press, 2011)
The study of mathematical cognition and the ways in which the ideas of space, time and number are encoded in brain circuitry has become a fundamental issue for neuroscience. How such encoding differs across cultures and educational level is of further interest in education and neuropsychology. This rapidly expanding field of research is overdue for an interdisciplinary volume such as this, which deals with the neurological and psychological foundations of human numeric capacity. A uniquely integrative work, this volume provides a much needed compilation of primary source material to researchers from basic neuroscience, psychology, developmental science, neuroimaging, neuropsychology and theoretical biology. * The first comprehensive and authoritative volume dealing with neurological and psychological foundations of mathematical cognition * Uniquely integrative volume at the frontier of a rapidly expanding interdisciplinary field * Features outstanding and truly international scholarship, with chapters written by leading experts in a variety of fields.
1. Mental magnitudes and their transformations -- 2. Neural codes for space, time and number -- 3. Shared mechanisms for space, time and number -- 4. Origins of proto-mathematical intuitions -- 5. Representational change and education.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Number concept -- Congresses; Cognitive neuroscience -- Congresses; Space and time -- Psychological aspects -- Congresses; Mathematics -- Psychological aspects -- Congresses; SCIENCE -- Cognitive Science; Cognitive neuroscience; Mathematics -- Psychological aspects; Number concept; Space and time -- Psychological aspects; Electronic books